Comparative toxicokinetics and toxicity of PFOA and its replacement GenX in the early stages of zebrafish. (December 2022) - Satbhai, Kruuttika; Vogs, Carolina; Crago, Jordan
Abstract: Per: and poly-fluoroalkyl substances (PFAS) are receiving attention due to their persistence, and potential adverse effects on environmental and human health. Efforts to reduce long-chained PFAS (≥C8) compounds were implemented in 2006 as a part of "PFOA Stewardship Program Initiative" (PFOA–perfluorooctanoic acid). Short-chained PFAS (<C8) were introduced as replacements, which were believed to have lower potential for environmental persistence and bioaccumulation. Little is known about the uptake and elimination, and potential toxic effects of these replacement compounds. Hence, it is important to compare toxicokinetics and toxicity of long-chain PFAS to their replacement compounds. To this end, zebrafish (ZF), Danio rerio, embryos were exposed to PFOA and its short-chain replacement perfluoro (2-methyl-3-oxahexanoic) acid (GenX) with the aim to assess uptake and elimination kinetics, hatching success, morphology, startle response, and survival. At 24 hpf, LC50 was 82 μM for PFOA and 170 μM for GenX. At 54 hpf, GenX but not PFOA showed an increase in hatching success. At 120 hpf, no statistically significant differences were seen in white light startle response below the LC50. PFAS internal concentrations were measured at 72 and 120 hpf during exposure phase, and at 168 hpf during depuration phase. GenX and PFOA internal concentrations in 120 hpf larvae exposed to highest concentration (20 μM) were 35.02 and 44.51 μM, respectively. Concentrations were eliminated almost completely at 168 hpf for GenX up to 95%, while for PFOA up to 50%. As steady-state was not reached, we estimated kinetic bioconcentration factors (BCFkin). BCFkin for GenX was lower than PFOA at equimolar concentrations. However, bioconcentration factors were higher at the lower exposure concentrations for both chemicals, suggesting a concentration-dependent uptake of PFASs. The predicted internal effect concentrations, accounting for the differences in bioconcentration factors, were 229 μM for GenX and 226 μM for PFOA, suggesting similar toxic potencies. Graphical abstract: Image 1 Highlights: A comparative study was conducted to assess toxicokinetics and toxicity of PFOA and its replacement GenX using embryo-larval zebrafish. Toxicity study showed: at 24 hpf, the observed LC50 was 82 μM for PFOA, and 170 μM for GenX. No statistically significant differences were seen in white light startle response or morphology, at 120 hpf, below the LC50 concentrations for each PFOA or GenX. Toxicokinetics' study showed that bioconcentration factors were higher at the lower exposure concentrations for both chemicals, suggesting a concentration-dependent uptake of PFAS. The predicted internal effect concentrations, accounting for the differences in bioconcentration factors, were 229 μM for GenX and 226 μM for PFOA, suggesting similar toxic potencies.